Evaluation of moral intelligence in prehospital emergency healthcare employees: The case of Bolu-Düzce - Güneşer, Ramazan; Kırımlıoğlu, Nurdan (Acta Bioethica, 2024)
Prehospital emergency healthcare employees are frequently faced with ethical problems. Moral intelligence, which is seen as a rising value in the field of health, is very important for prehospital emergency health employees to choose the best and right action ethically. This study aims to evaluate the moral intelligence of prehospital emergency healthcare employees and to determine whether moral intelligence parameters differ according to various socio-demographic characteristics. This study was conducted with 261 emergency medical personnel working in the ambulance service between November 2021 and February 2022. Participants showed high sensitivity to equality, empathy, moral intelligence, justice, tolerance, self-control, and kindness in the delivery of healthcare services. There were no significant differences between the groups in the scale dimensions in terms of gender, educational level, working hours, working systems, income level and having children. Single/widowed/divorced/separated participants had significantly higher levels of empathy (p=0.004), justice (p=0.039) and self-control (p=0.009) than married participants. The self-control levels of paramedics were found to be higher than those of health officers/nurses/midwives/others (p=0.015). The high sensitivity of employees towards moral intelligence parameters can play an effective role in solving both ethical issues and problems related to other moral intelligence parameters in the field of prehospital healthcare.